The philosophical meaning of the façade of the traditional Noble House of the Bugis Bone (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The former kingdom system in Bone has shaped social stratification within the Bugis community, influencing the differentiation in the facade design of traditional houses. The traditional houses of Bugis nobility in Bone exhibit architectural characteristics that reflect high social status and noble cultural values. This study aims to reveal the philosophical meanings manifested in the facade composition of traditional Bugis noble houses in Bone. A qualitative method with an exploratory phenomenological approach was employed, involving direct observation and in-depth interviews with homeowners. The study focuses on both tangible and intangible phenomena. Bone Regency was selected as the research site due to its representative role as the center of the largest Bugis kingdom in South Sulawesi. The sample consists of three types of noble houses: (1) Bola Saoraja (king's house), (2) Bola Salassa (royal official's house), and (3) Bola Sada (descendant's house), all of which maintain their original architectural forms. Findings indicate that Alliri Awa Bola, the lower part of the house, symbolizes the grandeur of the kingdom; Ale Bola, the main body of the house, represents the perfection of leadership qualities; and Timpa Laja, the roof section, embodies noble thoughts and the duty to care for society. Thus, the composition of the facade of the Bugis Bone noble house is interpreted as the embodiment of a large royal system that has character and protects its people.
Keywords: Bugis nobili; Facade composition; Philosophical meaning; Traditional architecture